2011
DOI: 10.1002/chem.201002586
|View full text |Cite
|
Sign up to set email alerts
|

PdII and PtII Complexes of 2‐(2′‐Pyridyl)‐4,6‐diphenylphosphinine: Synthesis, Structure, and Reactivity

Abstract: The coordination chemistry of the bidentate P,N hybrid ligand 2-(2'-pyridyl)-4,6-diphenylphosphinine (1) towards Pd(II) and Pt(II) has been investigated. The molecular structures of the complexes [PdCl(2)(1)] and [PtCl(2)(1)] were determined by X-ray diffraction, representing the first crystallographically characterized λ(3)-phosphinine-Pd(II) and -Pt(II) complexes. Both complexes reacted with methanol at the P=C double bond at an elevated temperature, leading to the corresponding products [MCl(2)(1H·OCH(3))].… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…(Figure 18). 42 For the C(1)P(1)C(5) angle, a value of 108.0(2)°was found in the platinum complex 22. Despite the fact that the large opening of the CPC angle reflects a significant disruption of the aromaticity and consequently a high reactivity of the P=C double bond, both 21 and 22 seem to be considerably more stable than the NIPHOS-containing Pd(II) and Pt(II) complexes described by Venanzi et al, as they can be isolated easily and do not show any particular degradation upon manipulation.…”
Section: Coordination To M(ii) Fragments;mentioning
confidence: 97%
See 1 more Smart Citation
“…(Figure 18). 42 For the C(1)P(1)C(5) angle, a value of 108.0(2)°was found in the platinum complex 22. Despite the fact that the large opening of the CPC angle reflects a significant disruption of the aromaticity and consequently a high reactivity of the P=C double bond, both 21 and 22 seem to be considerably more stable than the NIPHOS-containing Pd(II) and Pt(II) complexes described by Venanzi et al, as they can be isolated easily and do not show any particular degradation upon manipulation.…”
Section: Coordination To M(ii) Fragments;mentioning
confidence: 97%
“…Despite the fact that the large opening of the CPC angle reflects a significant disruption of the aromaticity and consequently a high reactivity of the P=C double bond, both 21 and 22 seem to be considerably more stable than the NIPHOS-containing Pd(II) and Pt(II) complexes described by Venanzi et al, as they can be isolated easily and do not show any particular degradation upon manipulation. 42,43 It is assumed that the additional phenyl substituents in the α-position of the heterocyclic framework might indeed contribute to a kinetic stabilization of the metal complex, as the P=C double bond is sterically more protected for addition reactions. This is an important contribution to the chemistry of phosphinines, as this aspect is relevant for further applications of 2,4,6-triarylphosphinines since such novel coordination compounds are now synthetically accessible for the first time.…”
Section: Coordination To M(ii) Fragments;mentioning
confidence: 99%
“…As a matter of fact, we could recently demonstrate for the first time that the reaction of the neutral phosphinine-M II complexes [(1)PdCl 2 ] and [(1)PtCl 2 ] with MeOH does not proceed randomly but quantitatively and selectively to the syn-addition product of type B (Figure 2) as confirmed by the X-ray crystal structure. [7] This indicates that the reaction proceeds in a concerted way, rather than in a two-step process. In contrast, we found that treatment of the cationic phosphinine-M III complexes [(1)Cp*RhCl]Cl and [(1)Cp*IrCl]Cl with water leads quantitatively and selectively to the anti-addition products 2 (Rh) and 3 (Ir), respectively (type C, Figure 2), as confirmed by crystal structure determinations.…”
Section: Introductionmentioning
confidence: 97%
“…[4] We have recently developed a facile synthetic route to 2-(2'-pyridyl)-4,6-diphenylphosphinine (1, Figure 1), which is readily available from the corresponding pyridyl-functionalized pyrylium salt. [5][6][7] It is by now well established that the coordination chemistry of phosphorus-analogues of 2,2'-bipyridines is markedly different from that of classical tertiary diphosphines or their all-nitrogen-counterparts. [8][9][10][11][12] In contrast to (bi)pyridines, phosphinine-based ligands are especially suitable for the stabilization of electron-rich metal centers due to the pronounced p-acceptor properties of the aromatic phosphorus heterocycle.…”
Section: Introductionmentioning
confidence: 99%
“…[16,17] With the neutral complex [(1)Cp*IrCl], the addition of water to the P=C double bond is reversible.…”
mentioning
confidence: 99%